Teachers’ Attitude towards the Learning Achievement of Students with Learning Disabilities in Inclusive Schools - Marlina Marlina; Tika Hendrawati; Grahita Kusumastuti (Department of Special Education, 2019)
Students who have learning disabilities are more often to get poor learning outcomes. One of several factors that affect the learning outcome is the teacher’s attitude. The research aims at finding the students’ opinions on teacher’s attitude towards the learning outcomes of students with learning disabilities in inclusive primary schools. This research applies quantitative approach. Data were collected using questionnaire and analyzed descriptively. The results showed that teachers accept the learning achievements of students with learning disabilities in cognitive aspect (77.93%), affective aspect (80.50%), and conative aspect (77.92%).